Combined Boyden-Flow Cytometry Assay Improves Quantification and Provides Phenotypification of Leukocyte Chemotaxis - Gomez-Lopez, Nardhy (Public Library of Science, 2011)
Chemotaxis has been studied by classical methods that measure chemotactic and random motility responses in vitro, but these methods do not evaluate the total number and phenotype of migrating leukocytes simultaneously. Our objective was to develop and validate a novel assay, combined Boyden-flow cytometry chemotaxis assay (CBFCA), for simultaneous quantification and phenotypification of migrating leukocytes. CBFCA exhibited several important advantages in comparison to the classic Boyden chemotaxis assay (CBCA): 1) improved precision (intra-assay coefficients of variation (CVs): CBFCA-4.7 and 4.8% vs. CBCA-30.1 and 17.3%; inter-observer CVs: CBFCA-3.6% vs. CBCA 30.1%); 2) increased recovery of cells, which increased assay to provide increased sensitivity; 3) high specificity for determining the phenotype of migrating/attracted leukocytes; and 4) reduced performance time (CBFCA 120 min vs. CBCA 265 min). Other advantages of CBFCA are: 5) robustness, 6) linearity, 7) eliminated requirement for albumin and, importantly, 8) enabled recovery of migrating leukocytes for subsequent studies. This latter feature is of great benefit in the study of migrating leukocyte subsets. We conclude that the CBFCA is a novel and improved technique for experiments focused on understanding leukocyte trafficking during the inflammatory response.